Grassland Dynamics and the Driving Factors Based on Net Primary Productivity in Qinghai Province, China - Xiaoxu Wei; Changzhen Yan; Wei Wei (ISPRS International Journal of Geo-Information, 2019)
Qinghai province is an important part of the Tibetan Plateau, and is characterized by extremely fragile ecosystems. In the last few decades, grasslands in this province have been influenced profoundly by climate change, as well as human activities. Here, we use the Carnegie-Ames-Stanford Approach (CASA) model to assess the dynamics of temperate steppe, alpine steppe, temperate meadow, alpine meadow, sparse grassland and herbaceous wetland via actual net primary productivity (NPPa). Our findings showed that: (1) From 2001 to 2016, the average NPPa in Qinghai province showed a fluctuation presented a generally increasing trend. The mean value of NPPa was 114.27 g C m−2 year−1, and the increase rate was 0.47 g C cm−2 year−1. (2) There were NPPa increase rate discrepancies among the six typical grassland biomes. Herbaceous wetland had the highest change rate, closely followed by alpine steppe, temperate steppe, alpine meadow, temperate meadow and sparse grassland. (3) The largest area of restoration mainly impacted by climate change reached 47.08% of the total grassland area, with human activities accounting for 21.74%. By contrast, the deteriorated area induced by human activities accounted for 9.78% of the total grassland. (4) Temperature may have been a greater factor than precipitation in driving grassland change during the study period. Decreasing grazing intensity and implementing effective protection measures were favorable to grassland restoration.